Failure of interferon gamma to induce the anti-inflammatory interleukin 18 binding protein in familial hemophagocytosis. - Claudia A Nold-Petry; Thomas Lehrnbecher; Andrea Jarisch; Dirk Schwabe; Josef M Pfeilschifter; Heiko Muhl; Marcel F Nold; Marcel F Nold (PLoS ONE, 2010)
BACKGROUND: Familial hemophagocytosis (FHL) is a rare disease associated with defects in proteins involved in CD8+ T-cell cytotoxicity. Hyperactivation of immune cells results in a perilous, Th1-driven cytokine storm. We set out to explore the regulation of cytokines in an FHL patient who was clinically stable on low-dose immunosuppressive therapy after bone marrow transplantation over a six-month period. During this period, chimerism analyses showed that the fraction of host cells was between 1 and 10%. Both parents of the patient as well as healthy volunteers were studied for comparison. METHODS/PRINCIPAL FINDINGS: Using ELISA, quantitative real-time PCR, and clinical laboratory methods, we investigated constitutive and inducible cytokines, polymorphisms, and clinical parameters in whole blood and whole blood cultures. Although routine laboratory tests were within the normal range, the chemokines IP-10 and IL-8 as well as the cytokine IL-27p28 were increased up to 10-fold under constitutive and stimulated conditions compared to healthy controls. Moreover, high levels of IFNgamma and TNFalpha were produced upon stimulation. Unexpectedly, IFNgamma induction of IL-18 binding protein (IL-18BP) was markedly reduced (1.6-fold vs 5-fold in controls). The patient's mother featured intermediately increased cytokine levels, whereas levels in the father were similar to those in the controls. CONCLUSIONS/SIGNIFICANCE: Since IL-18 plays a major role in perpetuating hemophagocytosis, the failure of IFNgamma to induce IL-18BP may constitute a fundamental pathogenetic mechanism. Furthermore, increased production of IL-8 and IL-27 appears to be associated with this disease. Such dysregulation of cytokines was also found in the heterozygous parents, providing a novel insight into genotype-phenotype correlation of FHL which may encourage future research of this rare disease.